Moderate conformational transition promotes the formation of a self-reinforced highly oriented silk fibroin network structure. Issue 42 (13th October 2021) - Shu, Ting; Cui, Jing; Lv, Zhuochen; Cao, Leitao; Ren, Jing; Ling, Shengjie
Abstract : Moderate conformation transition promotes the formation of low-density crosslinking molecular network and further rearrangement of amorphous proteins to form the highly oriented molecular network structure, which paved the way for achieving mechanical-enhanced silk fibroin materials. Abstract : A highly oriented molecular network structure (HOMNS) is a common and favorable design in natural and regenerated silks to achieve self-reinforcement of the material. However, the fundamental issues related to the formation of the HOMNS in silk fibroin materials and its influence on mechanical performance have not yet been addressed. By combining experimental characterization and molecular dynamics simulation, this work revealed that moderate conformational transition of silk fibroin promoted the formation of a low-density crosslinking molecular network among proteins. Such a molecular network is beneficial to further rearrangement of amorphous proteins in subsequent processing to form HOMNS. Here, a structure was confirmed that can strengthen the materials several times compared with the same material without HOMNS. These investigations improved the in-depth understanding of the fundamental questions related to the silk fibroin assembly, revealed their crucial structural remodeling, and paved the way for new fabrication strategies of mechanical-enhanced silk fibroin materials.